PEMIKIRAN SYEKH NAWAWI AL-BANTANI TENTANG AKIDAH ASY'ARIYAH RELEVANSI KONTEMPORER DI NUSANTARA - Hilda Mirza Syani; Ayu Restiani; Munawaroh Munawaroh (LPPI Universitas Al-Qolam Malang, 2025)
Abstract : This study examines the views of Sheikh Nawawi Al-Bantani on the Ash'ariyah creed and its relevance in the context of religious life in the archipelago today. This study is motivated by the significant role of Sheikh Nawawi as a scholar from the archipelago who made a major contribution to the development of Sunni Islamic theology, especially through the Ash'ariyah approach which is known to be moderate and inclusive. The focus of this study is to explore the characteristics of Sheikh Nawawi's kalam thought in central issues of creed, such as the concept of the oneness of God (wahdaniyyah), divine will and power, and understanding of Allah's kalam. In addition, this study also highlights the relevance of these views in the religious practices of contemporary Indonesian society. The research was conducted through a library research method with a qualitative approach, utilizing the works of Sheikh Nawawi and supporting secondary references. The findings show that Sheikh Nawawi developed classical Ash'ariyah kalam thought that emphasized the aspects of monotheism, the absolute power of God, and the existence of a synthetic approach between Ash'ariyah and Maturidiyyah thought in explaining Allah's kalam. This thought has proven to be still relevant in shaping the character of Islam Nusantara which is moderate, tolerant, and open to local culture. In conclusion, Sheikh Nawawi's thoughts not only enrich the discourse of Islamic theology, but also provide an important foundation for the development of peaceful and contextual Islam in today's Indonesia.